Exploring Hidden Paths: Tax Strategies in Transportation through Leverage, Liquidity, and Total Assets - Mubarok, Faizul; Pamungkas, Farhan; Pangestu, Ilham; Firdaus, Paja Zaky (Jurnal Eksplorasi Akuntansi, 2025)
This study analyzes the impact of total assets, debt-to-equity ratio (DER), debt-to-asset ratio (DAR), current ratio, and crisis on corporate tax aggressiveness in the transportation sector. The research sample comprises 12 transportation companies, with financial statement data from the Indonesia Stock Exchange from 2018-2022. The panel data regression method was used for analysis. The results showed that debt-to-asset ratio (DAR), debt-to-equity ratio (DER), and total assets significantly impact corporate tax aggressiveness in the transportation sector. On the other hand, current ratio and crisis variables do not affect tax aggressiveness. These findings contribute to the understanding of factors that influence the tax strategies of transportation companies in Indonesia, particularly highlighting the importance of capital structure and firm size in the context of tax aggressiveness.